Artery pseudoaneurysm per screw wound Superficial femoral osteosynthesis - Abó, Juan C; Gateño, Nisso; Estefan, Alberto; Franco, Avelino (Cirugía del Uruguay, 1974)
After 9 years of carrying Milch's plate a patient developed a pseudoaneurism of superficial femoral artery as a consequence of a wound caused by an osteosynthesis screw. This etiology in formation of arterial pseudoaneurisms is rare and no reference to any other such case has been found in bibliography.